A CORPUS-BASED ANALYSIS OF CRITICAL STRATEGIES in COVID-19 CORPORA - Muslimah, Ryza Wahyu (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2020)
The aim of this study is expected to find whether the word critical frequently modifies COVID-19 or HIV, and are the type of critical strategies that frequently appear on the corpora.COVID-19 becomes the outbreak issue which is considered as a big problem from everyone in the world. It spreads rapidly from human to human. COVID-19 does not repute as something trifled, because it zaps undetected person in person. Besides, the existence of HIV still becomes the specter of today’s issues. These phenomena summon everyone to conduct the research in a medical perspective or even associate the result in a linguistic perspective. To reach further expanding, mixed method or commonly is used to call as quantitative and qualitative collaboration method. The result showed the T-score of COVID-19 > P value (4.548827 > 1.658). Hence, the proof meant word critical was most significantly modified COVID-19 rather than HIV. Besides, other result represent indirect criticism as the most frequent presence of critical strategies, by the keywords ‘coronavirus may’ displayed 137 (0.49 per million) tokens, ‘ coronavirus is quite’ displayed 3 (0.01 per million) tokens, and ‘coronavirus probably’ displayed 8 (0.03 per million) tokens. Keywords: Corpus-Based Analysis, Critical Strategies, COVID-19